Rancang Bangun Penyediaan Rekam Medis Tanpa Cover Pasien Rawat Jalan Berbasis Web di RSD Mangusada Kabupaten Badung - I Wayan Swartana; Bambang Hadi Kartiko; Agus Tommy Adi Prawira Kusuma (Jurnal PRIMA, 2022)
The development of the world of information technology is so fast and widespread throughout the world, so this will have an impact on the activities of institutions, especially those that use information technology facilities so that it will increase the efficiency and effectiveness of the performance of government, private and individual institutions including health institutions. Based on the results of observations made by the author, the number of patient visits at the Mangusada Hospital, Badung Regency reached 4,185 patients, the average medical record of patients without cover per day was 135 medical records. The number of medical records of patients without a cover who are controlled again per day is 55 medical records. Searching for medical records of patients without cover at the Mangusada Hospital, Badung Regency is still done manually, namely by sorting out the medical records one by one. The system built using the SDLC method in the development of a web-based system. Based on the results of the usability test conducted, the system is classified as very good for implementation.